-2(2c-4)=

Simple and best practice solution for -2(2c-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2c-4)= equation:


Simplifying
-2(2c + -4) = 0

Reorder the terms:
-2(-4 + 2c) = 0
(-4 * -2 + 2c * -2) = 0
(8 + -4c) = 0

Solving
8 + -4c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -4c = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -4c = 0 + -8
-4c = 0 + -8

Combine like terms: 0 + -8 = -8
-4c = -8

Divide each side by '-4'.
c = 2

Simplifying
c = 2

See similar equations:

| 1.8y=3.8 | | 9x^3/2-18=0 | | 0=x^2+3x+8 | | V/6.3=-7 | | 0=x+3x+8 | | f(x)=(x-4)(x+2) | | 2z^2-21z+3=39 | | (1/7)x=8 | | n=25+0.45n | | R=-30n^2+180n+3360 | | xsquared+15=24 | | (4x^2)-6x+3=0 | | 6(8+x)=48-11x | | 2c-12c= | | 6[2-(-3x-2)]=68x+99 | | 24+6-12x=60 | | -7.3t^2+8.25t+2.1=H | | 13(x-5)=12x-69 | | -88=8(1-4x) | | -7.3t^2+8.25t+2.1=x | | 1.63q=9.73 | | 8(a+7b-5)=8a+56b-72 | | 7=56y | | -7.3t^2+8.25+2.1=x | | 2x-7=2y-13 | | 3x^3y^4+18x^2y^4-6x^2y^4-36xy^4=0 | | 1.7=2.38 | | |z|=-1/5 | | 4a/-8=24 | | 5/8÷15/32 | | Ln*(x-1)-(ln*x)=3+(ln*3) | | -3(5b-3)=99 |

Equations solver categories